An Analysis of Isolated Vowels in the Subdialect of Lukšiai - Bacevičiūtė, Rima (Kalbotyra, 2000)
The article examines the spectra of isolated vowels, their acoustic features, articulation and their relationship with Jones’ cardinal vowels.The spectral analysis and the acoustic data allows us to claim that marked extreme articulation is not typical of the vowels and that the range of the horizontal and vertical movement of the tongue is not wide. The majority of the low vowels are found in the lower part of the traditional vowel trapezium. For front vowels, more important is pronunciation sequence; for back vowels, more important is the rise of the tongue. The vowels of the subdialect are much closer to cardinal secondary than to cardinal primary vowels. There are more prints of similarity between their acoustic and articulative properties.The most distinct extreme articulation is peculiar to the front, high vowel [i.]. However, even this vowel cannot compare with the cardinal vowels of similar articulation. As for F1 and F2 meanings, this vowel is closest to the cardinal secondary labial vowel [ø:]. One can surmise, then, that the vowel [i.] is somewhat labialized, too. Notable is also the vowel [e̤.]: it has a rather high F2 and a comparatively low F1. As a result, it is diffusive, closed and high. By their position the short-tenseless [i], [u] stand out in the vowel system. The vowel [i] is higher and more back than the vowel [o.].Certain differencies can be observed in the low vowels of different origin: vowels of historical origin are higher and closer than the corresponding positional-length vowels. The reason for this must be the surviving traces of nasalization. The vowel [æ.] corresponds in meaning to the vowel [a.], which shows how it is open and how it differs from the vowel [e.].The indices of the tenseness of the lower vowels confirm linguists’ premises that tenseness, as an acoustic feature, is essential only to non-high vowels while the determinant feature of low long-tense vowels is duration.